Kodifikasi Hadis: Menelusuri Fase Penting Sejarah Hadis Nabawi - Ahmad Tholabi Kharlie (Refleksi: Jurnal Kajian Agama dan Filsafat, 2005)
The long and winding historical journey of the Prophetic Hadith has placed it as a subject that is never devoid of controversy and discourse disputes. One of the crucial issues often debated across various circles revolves around the history of the writing and compilation of Hadith. Indeed, discourse regarding this codification has been wielded as a potent weapon by Orientalists and those who deny the Sunnah (a group opposing the Sunnah) to discredit the Hadith or Sunnah and challenge its authenticity as the second source of Islamic law after the Quran. The contention among Muslims, as criticized by Orientalists, revolves around the issue of the validity of the writing and compilation of Hadith when viewed from normative considerations (such as the sayings of the Prophet, the reports of the Companions, and the followers), ultimately leading to doubts about the authority of the Sunnah itself within the broader framework of Islamic Law. This paper aims to provide initial clarification on the pros and cons surrounding the codification of the Prophetic Hadith.